Brief Report: Alternative Splicing of Extra Domain A (EIIIA) of Fibronectin Plays a Tissue‐Specific Role in Hematopoietic Homeostasis. (4th May 2016) - Malara, Alessandro; Gruppi, Cristian; Celesti, Giuseppe; Romano, Bina; Laghi, Luigi; De Marco, Luigi; Muro, Andrés F.; Balduini, Alessandra
Abstract : Fibronectin (FN) is a major extracellular matrix protein implicated in cell adhesion and differentiation in the bone marrow (BM) environment. Alternative splicing of FN gene results in the generation of protein variants containing an additional EIIIA domain that sustains cell proliferation or differentiation during physiological or pathological tissue remodeling. To date its expression and role in adult hematopoiesis has not been explored. In our research, we demonstrate that during physiological hematopoiesis a small fraction of BM derived FN contains the EIIIA domain and that mice constitutively including (EIIIA +/+ ) or excluding (EIIIA −/− ) the EIIIA exon present comparable levels of hematopoietic stem cells, myeloid and lymphoid progenitors within BM. Moreover, only minor alterations were detected in blood parameters and in hematopoietic frequencies of BM granulocytes/monocytes and B cells. As opposed to other tissues, unique compensatory mechanisms, such as increased FN accumulation and variable expression of the EIIIA receptors, Toll like receptor‐4 and alpha9 integrin subunit, characterized the BM of these mice. Our data demonstrate that FN is a fundamental component of the hematopoietic tissue and that the EIIIA exon may play a key role in modulating hematopiesis in conditions of BM stress or diseases. Stem Cells 2016;34:2263–2268 Abstract : Mice with a different splicing of Extra domain A (EIIIA) of fibronectin revealed a tissue specific role for this cellular isoform of fibronectin in the regulation of hematopoietic homeostasis. Constitutive inclusion or deletion of the EIIIA exon of fibronectin in mice(A) result in altered levels of fibronectin and receptors, and changes in cell frequencies within bone marrow(B) (Scale Bar = 50 μm). On the contrary, aberrant splicing of cellular EIIIA fibronectin, does not influence spleen homeostasis(C) (Scale Bar = 100 μm).